Orthodontic pain in maxilla and mandible during the first week of orthodontic treatment - Juloski Jovana; Vasović Dina; Vučić Ljiljana; Pajević Tina; Glišić Branislav (Balkan Stomatological Society, 2022)
Background/Aim: This investigation aimed to evaluate the intensity of self-reported pain and frequency of self-medication with analgesics during the initial phase of orthodontic treatment with fixed appliances and to compare possible differences between the maxillary and mandibular teeth. Material and Methods: In this observational clinical trial 68 patients had similar orthodontic forces (the same bracket-slot and prescription, archwire size and material, and treatment plan) applied on maxillary and mandibular teeth. The patients recorded pain intensity and use of analgesics for the first seven days of treatment. Comparisons between maxillary and mandibular teeth regarding the pain intensity and self-medication frequency were performed by Wilcoxson Signed Ranks Test and McNamara Test for Matched Pairs, respectively. Results: The patients reported moderate pain in both jaws which decreased significantly with each day of treatment. Still, during the initial three days of treatment intensity of pain for maxillary teeth was significantly lower compared to the mandibular teeth. Patients reported analgesics consumption for both jaws, without a statistically significant difference between them. Conclusions: The patients have reported orthodontic pain of higher intensity in the mandibular arch compared to the maxillary arch during the initial phase of orthodontic treatment with fixed appliances.